SMEs performance and interaction of knowledge management, human capital and finance access - Halim Bin Mad Lazim, Khansa Masood, Mohd Noor B Mohd Shariff, (Opción, 2019)
This study presents a conceptual framework that proposes the positive influence of human capital and knowledge management on SMEs performance in the environment of Pakistan via comparative qualitative research methods. As a result, access to finance moderates the relationship between Human Capital and SMEs performance and access to finance moderates the relationship between Knowledge Management and SMEs performance. In conclusion, the role of competition in determining firms’ performance demands studies that examine the competition beyond the conventional approach of competition directly affecting the performance.